The influence of methylphenidate on heart rate and brain connectivity - Van Breda, Keelyn (MRC/UCT RU for Exercise and Sport Medicine, 2018)
The central governor model (CGM) proposes that muscle recruitment is regulated by the brain through subconscious homeostatic control of afferent feedback. It has been suggested that the dopaminergic system plays a key role in the CGM, with dopaminergic activation leading to lower fatigue thresholds. Key neural circuits, including the central autonomic network (CAN), may also play a role in altering thresholds by reducing conscious bodily awareness, known as interoception. However, few studies have directly examined the dopaminergic neurotransmitter system and CAN connectivity, during exercise-induced fatigue. Although there is reason to suspect that subjects with high activity (HA) and low activity (LA) levels have different fatigue thresholds, potential differences in dopaminergic function and related circuity have not been compared across these groups. In this thesis, I was therefore interested in examining the impact of a dopaminergic agent, methylphenidate (MPH) on: a) brain connectivity at rest before exercise and during exercise, b) on heart rate (HR) at rest before exercise and during exercise. Furthermore, c) I was interested in whether the effect of MPH administration (MA) on HR and functional connectivity (FC), between CAN regions, pre-exercise impacted HR and FC during exercise and whether this differed between HA and LA subjects. In order to measure the effect of MA on brain connectivity at rest and during exercise I used a functional magnetic resonance imaging (fMRI) scanner. To measure the effect of MA on fatigue thresholds, I used a MRI compatible handgrip device which recorded grip force output during a fatiguing handgrip task. To measure HR before and during handgrip exercise I used a MRI compatible electrocardiogram (ECG) machine. My first study aimed to determine the effect of MA on resting state (R-fMRI) FC between CAN regions and its correlation with HR before exercise. My second study aimed to see the effect of MA on task HR, force output and, FC and EC between CAN regions, during a fatiguing handgrip task. My third study aimed to see the effect of MA on the relationship between HR and FC pre-exercise and HR and FC during exercise and whether this differed between LA and HA subjects. I found that: 1.) MA decreased R-fMRI FC between CAN regions, and that this was associated with an increase in HR during resting state 2.) MA decreased FC between CAN regions with an associated increase in task HR and force output during a fatiguing handgrip task 3.) After MA, R-fMRI FC determines task FC independent of HR 4.) MA significantly increased task HR in LA but not HA subjects 5.) After MA, R-fMRI FC determines task FC independent of HR in LA but not HA subjects. Taken together, the functional uncoupling of CAN regions and increased HR after MA suggests that MA increases the fatigue threshold by diverting attention away from interoceptive cues, such as HR. However, this finding may be more relevant in LA subjects, where MA is also associated with increased HR during exercise.